Elastic electron scattering from 17Ne and 27P exotic nuclei - Ridha, A. R. (Iraqi Journal of Physics, 2019)
The ground state proton, neutron and matter densities andcorresponding root mean square radii of unstable proton-rich 17Neand 27P exotic nuclei are studied via the framework of the twofrequencyshell model. The single particle harmonic oscillator wavefunctions are used in this model with two different oscillator sizeparameters core b and halo , b the former for the core (inner) orbitswhereas the latter for the halo (outer) orbits. Shell model calculationsfor core nucleons and for outer (halo) nucleons in exotic nuclei areperformed individually via the computer code OXBASH. Halostructure of 17Ne and 27P nuclei is confirmed. It is found that thestructure of 17Ne and 27P nuclei have 25 / 2 (1d ) and 1/ 2 2s -dominantconfigurations, respectively. Elastic electron scattering form factorsof these exotic nuclei are also studied using the plane wave Bornapproximation. Effects of the long tail behavior of the proton densitydistribution on the proton form factors of 17Ne and 27P areanalyzed. It is found that the difference between the proton formfactor of 17Ne and that of stable 20Ne (or of 27P and that of stable31P) comes from the difference in the proton density distribution ofthe last two protons (or of the last proton) in the two nuclei. It isconcluded that elastic electron scattering will be an efficient tool (inthe near future) to examine proton-halo phenomena of proton-richnuclei.